Statistical analysis with R : beginner's guide : take control of your data and produce superior statistical analyses with R - Quick, John M. (Packt Pub., 2010)
Annotation This is a practical, step by step guide that will help you to quickly become proficient in the data analysis using R. The book is packed with clear examples, screenshots, and code to carry on your data analysis without any hurdle. If you are a data analyst, business or information technology professional, student, educator, researcher, or anyone else who wants to learn to analyze the data effectively then this book is for you. No prior experience with R is necessary. Knowledge of other programming languages, software packages, or statistics may be helpful, but is not required.
Keywords: Mathematical statistics -- Data processing.; R (Computer program language); Statistics -- Data processing.; elektronické knihy; electronic books